Does Digital Terrorism Really Exist? - Buresh, Donald L. (Journal of Advanced Forensic Sciences, 2020)
This paper attempts to answer the question of whether digital terrorism, also known as cyberterrorism, exists. The paper defines terrorism both in the conventional and digital sense. It then gives a short history of conventional terrorism, dating back two thousand years and ending with the terrorist activities in several third-world nations. The essay then discusses digital terrorism, highlighting the Estonian, Georgian, and Ukrainian cyber-attacks. The work concludes that digital terrorism does indeed exist, but that the future is uncertain in the sense that future cyber-attacks will probably not resemble past attacks as the technology advances.
Keywords: Conventional terrorism; Cyber terrorism; Digital terrorism; Estonian cyber-attack; Georgian cyber-attack; Ukrainian cyber-attack